Cross-cultural da’wah: Internalization of hadith in the oral traditions of Urang Sunda - Risdayah, Enok; Paryati, Paryati; Fitri, Susanti Ainul; Rustandi, Ridwan; Aisyah, Siti (Jurnal Ilmu Dakwah, 2025)
Purpose – This study aims to comprehensively examine how Sundanese idioms and oral traditions effectively transmit Islamic values derived from hadith within the context of cross-cultural da'wah Method – This research employs a qualitative method with a descriptive approach, specifically utilizing content analysis and thematic analysis techniques to examine the intersection of Sundanese cultural idioms and Islamic hadith in da'wah practices. Result – The Sundanese oral tradition in the form of proverbs is a form of local intelligence in understanding hadith as a source of Islamic teachings, which functions as a cross-cultural communicative competence to avoid misunderstandings due to differences in expectations, worldviews, and values. Cross-cultural da'wah emphasises the universality of Islam that transcends geographical and socio-cultural boundaries, leveraging universal human similarities and the dynamics of cultural change to convey Islamic messages to diverse community groups effectively. Implication – The transformation of Arabic hadith into Sundanese proverbs shows that Islamic preaching can succeed when religious messages are communicated through local cultural forms familiar to the local community, without changing the essence of the teachings. The cross-cultural approach to da'wah through local oral traditions proves that Islam has a universal nature that can adapt to various socio-cultural contexts, thereby facilitating the acceptance and practice of Islamic teachings in the daily lives of the Sundanese people. Originality/Value – This study addresses a critical gap in existing literature by providing the first comprehensive analysis of the direct relationship between Sundanese idioms and hadith within the specific context of da'wah, offering a novel holistic approach that considers deeply rooted local cultural factors in Sundanese society. *** Tujuan – Penelitian ini bertujuan untuk secara komprehensif mengkaji bagaimana idiom-idiom Sunda dan tradisi lisan secara efektif menyampaikan nilai-nilai Islam yang berasal dari hadis dalam konteks da'wah lintas budaya. Metode – Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif, khususnya dengan teknik analisis konten dan analisis tematik untuk mengkaji perpaduan antara idiom-idiom budaya Sunda dan hadis Islam dalam praktik da'wah. Hasil – Tradisi lisan Sunda dalam bentuk peribahasa merupakan bentuk kecerdasan lokal dalam memahami hadis sebagai sumber ajaran Islam, yang berfungsi sebagai kompetensi komunikatif lintas budaya untuk menghindari kesalahpahaman akibat perbedaan ekspektasi, pandangan dunia, dan nilai-nilai. Da'wah lintas budaya menekankan universalitas Islam yang melampaui batas geografis dan sosio-budaya, memanfaatkan kesamaan manusia universal dan dinamika perubahan budaya untuk menyampaikan pesan-pesan Islam secara efektif kepada kelompok masyarakat yang beragam. Implikasi – Transformasi hadis Arab menjadi peribahasa Sunda menunjukkan bahwa dakwah Islam dapat berhasil ketika pesan-pesan agama disampaikan melalui bentuk-bentuk budaya lokal yang familiar bagi komunitas setempat, tanpa mengubah esensi ajaran tersebut. Pendekatan lintas budaya dalam dakwah melalui tradisi lisan lokal membuktikan bahwa Islam memiliki sifat universal yang dapat beradaptasi dengan berbagai konteks sosio-budaya, sehingga memudahkan penerimaan dan penerapan ajaran Islam dalam kehidupan sehari-hari masyarakat Sunda. Orisinalitas/Nilai – Studi ini mengatasi celah kritis dalam literatur yang ada dengan menyediakan analisis komprehensif pertama tentang hubungan langsung antara peribahasa Sunda dan hadis dalam konteks khusus dakwah, menawarkan pendekatan holistik baru yang mempertimbangkan faktor budaya lokal yang mendalam dalam masyarakat Sunda.